A method for effect modifier assessment (EMA) in ergonomic intervention research. (October 2018) - Edwards, Kasper; Winkel, Jörgen
Abstract: The numerous opportunities for effect modifications pose a major challenge in ergonomic intervention research. Even studies in systematic reviews that are assessed as being of high quality generally lack any proper consideration of the potential effect modifiers. We have developed a method for effect modifier assessment (EMA) in intervention research. The EMA method uses a participatory workshop consisting of representatives from all occupational groups in the investigated organization. The workshop identifies both intervention and modifier events including "confounders" and "effect modifiers" according to epidemiologic terminology. These are categorized into themes, then analyzed and evaluated for their potential effects on the investigated outcomes. The overall impact of the pooled modifier themes is finally estimated in relation to the estimated impact of the intervention events. In the present study, the EMA method was tested in two cases. The findings suggest that it provides information that strengthens inferences about the impact of the investigated ergonomic interventions. Further evaluation of the method is recommended. Highlights: The method identifies potential effect modifiers in ergonomic intervention research. The method estimates the potential impact of both interventions and modifiers. The method is tested in two cases; the potential effect modification is identified.